Financial Distress Memoderasi Pengaruh Antar Pengungkapan Sustainability Report Dan Konservatisme Pada Perusahaan Perbankan Yang Terdaftar Di Bei Periode 2019-2022 - Junaid, Asriani; Wahyuni, Nur; Kahfi, Zul; Salim, Ema Sapira (Jurnal Online Manajemen ELPEI, 2024)
The aim of this research is to determine whether financial distress moderates the influence between sustainability report disclosure and conservatism. Meanwhile, financial distress is measured using the Altman Z-score proxy and sustainability reporting is measured using the SRDI proxy, and conservatism is measured using the CONACC proxy. The research population is banking companies listed on the Indonesia Stock Exchange for the period 2019 - 2022. The research sample was 14 banking companies. Data analysis uses path analysis. Data processing uses the SmartPLS 4 program. The research results show that (1) sustainability reports have a negative and insignificant effect on conservatism. and (2) sustainability reports have a positive and insignificant effect on conservatism, moderated by financial distress